Factors Affecting the Change of ART Regimens at Pathum Thani Hospital - Thearawiboon, Wannasith (Journal of Health Science of Thailand, 2018)
The objectives of this retrospective descriptive study were to investigate the factors affecting antiretroviral regimen change. Retrospective analysis was made on data from medical records of HIV-infected patients receiving antiretroviral drugs at Patum Thani hospital during December 2003 - January 2008. Patient characteristics, epidemiological data, antiretroviral regimens, and relevant clinical data were collected. Of 388 patients includeded, 36.85 percent had changed the initial antiretroviral regimens. Important reasons of antiretroviral regimen change included adverse drug reactions (85.3%) in which 27 percent were drug rash; whereas 23.8 percent and 43.4 percent were hepatitis and lipodystrophy, respectively. Tuberculosis involved in 13.3 percent of the patients who changed antiretroviral regimen. Antiretroviral treatment failure was not found. In univariate analysis, ALT level was the only statistically significant factor between the patients with changed and unchanged regimens. In conclusion, the proportion of antiretroviral regimen change was approximately one third. Patients with a low ALT were more likely to have changed the initially prescribed antiretroviral drugs.